Glycaemic profiles of diverse patients with type 2 diabetes using basal insulin: MOBILE study baseline data. Issue 2 (17th November 2020) - Peters, Anne; Cohen, Nathan; Calhoun, Peter; Ruedy, Katrina J.; Beck, Roy W.; Martens, Thomas W.; Bao, Shichun; Njeru, Nelly M.; Beck, Stayce E.; Price, David A.
Abstract: Basal insulin is often prescribed to patients with suboptimally controlled type 2 diabetes (T2D); however, its therapeutic efficacy is inadequate in many. During the MOBILE study's baseline phase, we evaluated 173 participants' continuous glucose monitoring (CGM) data (mean ± SD age 57 ± 9 years; 50% female; HbA1c 9.1% [range 7.1%‐11.6%]; 40% using sulphonylureas; 19% using NPH; reported self‐monitored blood glucose [SMBG] frequency median 1.0 checks/day) who were using basal, but not prandial insulin. Blinded CGM data were recorded for 10 days prior to randomization. The mean glucose value was 208 ± 47 mg/dL and it was lowest in the early morning. Mean time in the 70‐180 mg/dL range was 9.6 ± 6.1 hours/day (40% ± 25%). Hyperglycaemia was extensive with medians of 14.7 (61%) and 5.0 (20.9%) hours/day with glucose greater than 180 and 250 mg/dL, respectively. Hypoglycaemia was infrequent (median [IQR] 0 [0, 4.3] minutes/day [0.0% 0.0%, 0.3%] with glucose less than 70 mg/dL). Blinded CGM highlights the limitations of infrequent SMBG in basal insulin users with T2D and allows characterization of hyperglycaemia and hypoglycaemia in basal insulin users with suboptimal control. The MOBILE study randomized phase will define the benefits of using real‐time CGM compared with SMBG in this population.